2021
DOI: 10.3390/brainsci11030322
|View full text |Cite
|
Sign up to set email alerts
|

Blood Serum Cytokines in Patients with Subacute Spinal Cord Injury: A Pilot Study to Search for Biomarkers of Injury Severity

Abstract: Background. Despite considerable interest in the search for a spinal cord injury (SCI) therapy, there is a critical need to develop a panel of diagnostic biomarkers to determine injury severity. In this regard, there is a requirement for continuing research into the fundamental processes of neuroinflammatory and autoimmune reactions in SCI, identifying changes in the expression of cytokines. Methods. In this pilot study, an extended multiplex analysis of the cytokine profiles in the serum of patients at 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Interestingly, the upregulation of proinflammatory cytokines TNFɑ and IL-1β persists in the serum 28 days after SCI in a rat, while IL-4 is downregulated at 28 days and there is no significant change in IL-10 at this timepoint [ 21 ]. However, Ogurcov et al [ 15 ] found a decreased concentration of both IL-1β and IL-10 in serum of human patients 14 days after SCI. Furthermore, they report the elevation of IL-4 and IFN-γ levels at this timepoint [ 15 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the upregulation of proinflammatory cytokines TNFɑ and IL-1β persists in the serum 28 days after SCI in a rat, while IL-4 is downregulated at 28 days and there is no significant change in IL-10 at this timepoint [ 21 ]. However, Ogurcov et al [ 15 ] found a decreased concentration of both IL-1β and IL-10 in serum of human patients 14 days after SCI. Furthermore, they report the elevation of IL-4 and IFN-γ levels at this timepoint [ 15 ].…”
Section: Main Textmentioning
confidence: 99%
“…However, Ogurcov et al [ 15 ] found a decreased concentration of both IL-1β and IL-10 in serum of human patients 14 days after SCI. Furthermore, they report the elevation of IL-4 and IFN-γ levels at this timepoint [ 15 ]. In general, analysis of cytokine in CSF and serum display similar patterns as the local response in injured spinal tissue (Figs.…”
Section: Main Textmentioning
confidence: 99%
“…We previously showed that UDI and ULM are applicable to human brain , both non-invasively in neonates 35 and adults 36 , and also during perioperative interventions in adult patients 37 . The precise analysis of vasculature state, along with other biomarkers previously described (blood serum cytokines, MRI, DTI [38][39][40][41] ) would provide a more complete picture of the pathophysiological changes in patients with various degrees of injury severity, and allow for a re ned/more accurate prognosis in view of the long-term follow up of these patients.…”
Section: Towards Patient's Strati Cation Using Udi and Ulmmentioning
confidence: 99%
“…The same considerations apply to nonprotein-based biomarkers such as cell-free DNA [ 40 ] and microRNAs [ 41 ]. We would add that these limitations, real or perceived, may also be time-dependent, with emerging research suggesting that cytokine measurements can be more useful during the postacute phase [ 42 ]. The risk of confounding peripheral responses can be easily mitigated, however, by focusing on nongeneric molecular biomarkers that have high CNS tissue specificity.…”
Section: Emerging Molecular Biomarkers For Stratification and Prognosis Of Spinal Cord Injurymentioning
confidence: 99%